2019
DOI: 10.15587/1729-4061.2019.171619
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a possibility to control the stressed­strained state of cylinder liners in diesel engines by the tribotechnology of alignment

Abstract: ress of friction and wear processes during operation largely depends on the properties of a lubricating environment and the films of antifriction materials formed at the working surfaces. In this case, the copper-containing materials are widely used for the surfaces of mating parts, operated under conditions of contact against high-temperature, abrasive-based substances. However, while possessing high electrical con-6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
(18 reference statements)
0
15
0
2
Order By: Relevance
“…The non-stable processes in the operation of friction nodes in automotive equipment in the presence of motor lubricants were considered in papers [6][7][8][9]. The experimental studies have established the effect of various additives to oils on the stabilization of friction forces and reducing the wear of rubbing surfaces.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The non-stable processes in the operation of friction nodes in automotive equipment in the presence of motor lubricants were considered in papers [6][7][8][9]. The experimental studies have established the effect of various additives to oils on the stabilization of friction forces and reducing the wear of rubbing surfaces.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The use of polymeric composites makes it possible to improve the wear resistance of working surfaces. Based on experimental research, authors of [14] constructed the model for predicting the mechanical behavior and reaction to damage in flat samples of composite materials. At the same time, the authors found no regularities in the influence of normal and tangential stresses on the wear of composite materials and their coatings.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…This ensures the necessary level of reliability. Various tests for researching and specifying the characteristics of tribojunction during liquid friction and viscous resistance were developed [4]. These tests are required for theoretical description of the friction process in the contact area in the presence of oil medium and description of the processes of interaction of oil with the working surface of parts.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%